2021
DOI: 10.1101/2021.01.22.427803
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social prediction modulates activity of macaque superior temporal cortex

Abstract: The ability to attribute thoughts to others, also called theory of mind (TOM), has been extensively studied. Computationally, the basis of TOM in humans has been interpreted within the predictive coding framework and associated with activity in the temporo-parietal junction (TPJ). However, the evolutionary origins of these human mindreading abilities have been challenged since the concept was coined. Here we identify a brain region in the Rhesus macaque that shares computational properties with the human TPJ. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…In monkeys, functional MRI studies have shown that this region responds selectively during observation of social scenes ( 19 ), and electrophysiological studies have demonstrated that single neurons in the mid-STS monitor other actions ( 20 ) and encode abstract strategic information and social context in monkeys choosing to cooperate or compete with a partner ( 21 ). On the basis of its computational and anatomical properties, this region has been identified as the precursor of the neural architecture supporting mentalizing, an ability central to social cognition in humans ( 22 , 23 ). The second cluster is primarily located in an antero-ventral part of the dysgranular subdivision of the insula ( 24 ) areas Id and Pi from the Saleem and Logothetis atlas ( 25 ), or areas dm, dv, and ap based on the architectonic organization of the insula proposed by Evrard and colleagues ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…In monkeys, functional MRI studies have shown that this region responds selectively during observation of social scenes ( 19 ), and electrophysiological studies have demonstrated that single neurons in the mid-STS monitor other actions ( 20 ) and encode abstract strategic information and social context in monkeys choosing to cooperate or compete with a partner ( 21 ). On the basis of its computational and anatomical properties, this region has been identified as the precursor of the neural architecture supporting mentalizing, an ability central to social cognition in humans ( 22 , 23 ). The second cluster is primarily located in an antero-ventral part of the dysgranular subdivision of the insula ( 24 ) areas Id and Pi from the Saleem and Logothetis atlas ( 25 ), or areas dm, dv, and ap based on the architectonic organization of the insula proposed by Evrard and colleagues ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the differential responses to the color of the central fixation were tightly linked to behavioral performance as the animals made significantly more errors when the two separate populations of instruction selective neurons lost their selectivity. These findings show that the GFP is involved in determining the relevance of the social cues such as faces and hands to behavior in nonverbal communications ( Ong et al, 2020 ) or predictability of social interactions ( Roumazeilles et al, 2021 ). mid-STS …”
Section: Temporal Cortex Attention Network (Tan)mentioning
confidence: 87%
“…In the right hemisphere, two supplementary STS activations are reported, STS 2 and STS 3. They are located posterior to the putative ML face patch and ventral to the gaze following patch reported in the dorsal posterior infero-temporal cortex 104 and possibly coincide with an area in the middle superior temporal cortex that has been recently described as modulated by the predictability of social interactions 105 , though this would have to be tested explicitly.…”
Section: Audio-visual Association Based On Social Meaning Possibly Re...mentioning
confidence: 90%